Socioeconomic Factor, Disaster Literacy and Disaster Awarness in Lampung Province - Simon Sumanjoyo Hutagalung; Himawan Indrajat; Deddy Hermawan (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Abstract. Natural disasters result in casualties owing to the community's lack of preparedness, this lack is a result of the education and catastrophe awareness condition among community groups. This paper describe the following questions: 1) How do socioeconomic factors affect disaster awareness? 2) Does a person's socioeconomic status effect their requirements and preferences for disaster information search? This study seeks to analyze a research issue utilizing case studies from two local administrations in the province of Lampung: South Lampung and Bandar Lampung. This research's is based on a comparative case study, an approach to community-based research that fits perfectly. Two-month survey (May-July 2022) will be undertaken to assess the level of disaster awareness in the community and to determine how and where individuals with varied socioeconomic levels get disaster-related information. The conclusion of this study is the importance for decision-makers to understand the background cultural context and disaster experience.